Religiosity and Learning Satisfaction among Students in the Islamic Religious Education Program - Putra, Roni Ahmad; Sujadi, Eko; Bustami, Yuserizal (JIE (Journal of Islamic Education), 2024)
Learning satisfaction is an essential aspect of the educational process and has become a central topic in many studies. This study investigates the effect of religiosity on student learning satisfaction. The researcher utilized a quantitative research method with a survey design. The Krejcie & Morgan formula was employed to ascertain the sample size, yielding 103 respondents out of 150 students enrolled in the Islamic Religious Education program at IAIN Kerinci for the Academic Year 2023/2024. The simple random sampling technique was applied to select the participants. Data collection was carried out using two research scales, namely the religiosity among muslims scale and the student course satisfaction questionnaire. The data collected was then analyzed using descriptive statistics and simple linear regression. The finding revealed that students' learning satisfaction and religiosity were high. Furthermore, it was found that religiosity significantly affected student learning satisfaction. These findings indicate that strong and active religiosity positively relates to learning satisfaction.